Umbilical Artery Thrombosis with Associated Acute and Severe Fetal Growth Restriction and Transient Severe Protein S Deficiency: Report of a Case with Prenatal Ultrasound Diagnosis Allowing for Timely Intervention and Good Outcome - Ali Alhousseini; Sunil Jaiman; Edgar Hernandez-Andrade; Salam Zeineddine; Faisal Qureshi; Suzanne M. Jacques (Case Reports in Obstetrics and Gynecology)
Background. Thrombosis of one of the umbilical arteries can be associated with adverse pregnancy outcomes such as stillbirth and severe intrauterine growth restriction (IUGR). Case. A 21-year-old gravida 1 patient, with a history of 3-vessel cord at 20 weeks, presented at 29 weeks with a single umbilical artery. The estimated fetal weight measurements at 26 weeks, 29 weeks, and 31 weeks were at the 27th percentile, the 26th percentile, and less than the 5th percentile, respectively. At 33 weeks, amniotic fluid index became abnormal at 2.3 cm and fetal heart tracing revealed spontaneous prolonged decelerations, and a cesarean delivery was performed. Placental pathology showed thrombosis of one of the umbilical arteries. At birth, a transient protein S deficiency was detected (activity 13%) and resolved at two months of age (activity 66%). The baby had an uneventful clinical course since birth. Conclusion. The recognition of reduction of umbilical arteries from two to one allowed for timely intervention with good outcome in this case. Thrombosis of umbilical vessels may be associated with a deficiency in coagulation proteins such as protein S.